Oncologic Imaging: Soft Tissue Tumors - Kang, Heung Sik; Hong, Sung Hwan; Choi, Ja-Young; Yoo, Hye Jin (Springer Singapore : Imprint: Springer, 2017)
This book helps readers to overcome the challenges encountered during the imaging diagnosis of soft tissue tumors due to their diversity and the significant overlap in imaging features between different tumors. It does so by fostering familiarization with typical findings and clearly explaining the pattern analysis of soft tissue tumors. The book opens with an overview of diagnostic considerations and discussion of the basic concepts of diagnostic imaging studies and histopathologic examinations. Grading and staging of soft tissue sarcomasare then described.In the second part of the book, radiologic features of soft tissue tumors are reviewed in detail, based on the 2013 WHO classification system.The third part summarizes diagnostic imaging clues, including characteristic imaging findings and radiologic signs that aid in specific diagnosis and differential diagnosis. The book closes by presenting 30 typical cases of soft tissue tumors, with questions, answers, and commentary, in order to help readers to consolidate what they have learned and to hone their diagnostic reasoning skills.
Keywords: Medicine.; Radiology.; Oncology.; Pathology.; elektronické knihy; electronic books